Verifikasi Metode Uji Lemak Pakan Buatan - Asmariani Asmariani; Amriani Amriani; Haslianti Haslianti (Universitas Sriwijaya, 2017)
Verification method is required to generate data analysis with accurate and precise value corresponding to the standrad method. This study aims to verify fat analysis method by using direct extraction method. The study was conducted in Laboratorium Pengujian, FPIK, Universitas Halu Oleo. Fat analysis method verified was direct extraction method or soxhlet method. The results showed that all precision values from experiments I-VIII, consisting of repeatability and reproductibility, have RSD values (0.03 – 0.14) lower than 2/3 RSD Horwitz (1.99). The accuracy results (% Recovery) indicated similarly RSD, lower than 2/3 RSD Horwitz (1.33). Based on these results, it can be concluded that fat analysis method used in Laboratorium Pengujian, meet the pecise and accuray standard, and generates valid data and accounted for.